Desenvolvimento sustentável: Para quem? Estudo de caso da ocupação das áreas de mananciais de São Bernardo do Campo - Lei 5.197/03 - Rizardi, Maria Lúcia de Souza (2005)
ABSTRACT This study aims at verifying if changes to the law for lot zoning in the Protected Areas of Billings Water Reservoir in the city of São Bernardo do Campo allows for the provision of sustainable development envisaged in the local government strategic plan. In this sense, the research looks into both the history of São Bernardo and that of the Reservoir; pointing at the multiple meanings that the concept (s) of sustainable development may arouse. If, on the one hand these multiple meanings may result in the arbitrary appropriation of the concept, on the other, it may bring about a number of different speeches. The study investigates some of these speeches with a view to providing greater consistency of thought within the proposal. Besides, it suggests a synchronicity between the new management world economic development and that one sought by São Bernardo; and examines the speeches of São Bernardo's mayor the author of the Bill number 137/03, and those of six councilors that took part in the Session that lead to Law number 5.197/03. The last chapter considers the case under study and briefly analyzes the problem under the light of Max Weber's theory. The study argues that sustainable development is a concept considered ideal type. So is the sustainable development proposal seen in São Bernardo thus the intricacy between economic growth and environmental preservation remais unanswered. At the same time, this research examines the conclict experienced between abiding to the ethics of conviction and the ethics of responsibility typical of political actions, social actions by definition. A brief investigation of reasoning found in the speeches of the investigated agents leads us to see the Ethical Irrationality of the World . We do grant that there may be sustainable development. However, one needs to clarify for who.